(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Annotation. The level of price on lands of agricultural purpose is the condition of efficient functioning of their market.The article proposes methodical approaches and projected calculation of level of price on lands of agricultural purpose in Ukraine on the basis of retrospective analysis of functioning of the market of lands of agricultural purpose and especially the level of prices in the beginning of the XX-th century. Methodical approaches as to the cost of land after its withdrawal from agricultural turnover are applied. Methodological principle of formation of price on land due to capitalization of the value of rent and on some economic indicators are proposed: correlation of crop and livestock products, export of agricultural products from 1 hectar of land, salary of workers in agriculture compared with European Union countries. The dynamics of changes of cost of lands in time is analysed.